2011
DOI: 10.1111/j.1551-2916.2011.04791.x
|View full text |Cite
|
Sign up to set email alerts
|

Irregular Electrical Conduction Types in Tin Oxide Thin Films Induced by Nanoscale Phase Separation

Abstract: The development of p‐channel tin oxide thin‐film‐transistors spurred the research into microstructural analysis of tin oxide phases and control of conduction type, as it is widely known that tin oxide thin films exhibit both n‐ and p‐type conduction depending on growth conditions. This study reports the relationship between the microstructural properties and the ambiguity of the electrical conduction type observed in nonstoichiometric tin oxides. Nonstoichiometric tin oxide thin films have been produced by RF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…Fabrication of SnO thin films has been extensively evaluated using a series of methods, including physical vapor deposition (PVD) routes, such as PLD, EB, RFMS, and DCMS using Sn, SnO, and SnO 2 targets on both rigid and flexible substrates. The Hall mobility and carrier (hole) concentrations, along with the deposition conditions are listed in Table 3 for relatively recent studies.…”
Section: Discovery and Synthesis Of Hole‐transporting (P‐type) Oxidessupporting
confidence: 74%
See 1 more Smart Citation
“…Fabrication of SnO thin films has been extensively evaluated using a series of methods, including physical vapor deposition (PVD) routes, such as PLD, EB, RFMS, and DCMS using Sn, SnO, and SnO 2 targets on both rigid and flexible substrates. The Hall mobility and carrier (hole) concentrations, along with the deposition conditions are listed in Table 3 for relatively recent studies.…”
Section: Discovery and Synthesis Of Hole‐transporting (P‐type) Oxidessupporting
confidence: 74%
“…Since then, SnO has been receiving increasing attention because of its relatively high Hall mobility and the abundance and nontoxic nature of tin . However, it is known that SnO has a fundamental stability issue, and it is very challenging to be deposited as a single‐phase thin film . The physical properties have mainly been reported from epitaxial SnO thin films deposited on (001) YSZ substrates by Ogo et al, including the optical bandgap ( E g ) of 2.7 eV by optical absorption measurements, and the fundamental (indirect) E g of 0.7 eV from the diffuse reflectance spectrum of SnO powder .…”
Section: Discovery and Synthesis Of Hole‐transporting (P‐type) Oxidesmentioning
confidence: 99%
“…Phase purity of the deposited films strongly depends on the deposition conditions like oxygen partial pressure, deposition rate, growth temperature and energy involved in the process. Slight deviation from the optimized conditions may result in mixed phasesof SnOwithmetallic Sn and/or SnO 2impurities.Phase separation between these phases can lead to irregular electrical conduction in the films[53].The first and the most important step in any PVD process is the selection of a suitable target material. Preparation of a ceramic target from SnO powder by conventional pellet pressing and sintering process is very difficult and always leads to impurity phases of SnO 2 and metallic Sn.Hosono et al employed spark plasma sintering process at 320 o C to get phase pure SnO ceramic target for pulsed laser deposition[49].…”
mentioning
confidence: 99%
“…This is because the hybridization of pseudo-closed Sn 5s and O 2p orbitals in SnO form delocalized and isotropic orbitals near the valence-band maximum (VBM), unlike in other p-type oxide semiconductors. This VBM structure provides an effective hole conduction path, thereby making SnO a potential candidate for the channel material of high mobility p-channel oxide TFTs [ 29 , 30 , 31 , 32 , 33 ]. In our previous report, we demonstrated that the formation of a Ni capping layer can increase the field-effect mobility ( μ FE ) of p-channel SnO TFTs.…”
Section: Introductionmentioning
confidence: 99%